Pareiorhina hyptiorhachis, a new catfish species from Rio Paraíba do Sul basin, Southeastern Brazil (Siluriformes, Loricariidae) - da Costa e Silva, Gabriel de Souza [UNESP] (2013)
Pareiorhina hyptiorhachis is described from Ribeirão Fernandes and Rio Pomba, Rio Paraíba do Sul basin, Brazil. The new species is distinguished from its congeners (P. brachyrhyncha, P. carrancas, P. cepta, and P. rudolphi) by the presence of a conspicuous ridge on the trunk posterior to the dorsal fin (postdorsal ridge), simple teeth, a completely naked abdomen, a round dorsal profile of the head, greater suborbital depth and greater head width. We discuss the distributional pattern of the new species and its congeners and hypothesize that headwater capture is responsible for the distribution of Pareiorhina species across different watersheds in southeastern of Brazil.